Muscle changes with high-intensity aerobic training in an animal model of renal disease - Togoe,Eliane Barbosa (2019)
Abstract Purpose: To analyze the muscle changes with high-intensity aerobic training (HIAT) in an animal model of renal disease (RD). Methods: Twenty one adult Wistar rats were divided into 3 groups: healthy sedentary (HS), RD sedentary (RDS), RD aerobic training (RDAT). RDS and RDAT were subjected to unilateral renal ischemia-reperfusion (10 min) and 21days after that, RDAT was subjected to 6 weeks HIAT (swimming). Serum creatinine (Cr) and muscle morphometry (cross-sectional area = CSA) of gastrocnemius were analyzed. Results: Cr was higher (p = 0.0053) in RDS (0.82 ± 0.04) than in the others (RDAT 0.55 ± 0.04; HS 0.55 ± 0.04). Morphometric analysis (class interval of CSA in μm2/absolute frequency of muscle fibers in each class) indicated that 50th percentile occurred in: HS 7th class (3000.00-3499.00/515), RDS, 8th class (3500.00-3999.00/484), RDAT 5th class (2000.00-2499.00/856). CSA of largest fibers in RDS, RDAT, HS was 9953.00 μm2, 9969.00 μm2,11228.00 μm2, respectively. High frequency of fibers with lower CSA occurred in 4th, 5th, 6th and 7th class in RDA, absence of fibers into 22nd, 23rd classes (RDS and RDAT). Conclusion: HIAT in an animal model of RD resulted in increased the number of muscle fibers with smaller CSA.